Justification for Interference? The Role of the Monroe Doctrine in the Stigmatization and Legitimation of Intervention in the US Foreign Policy in the 19th and Early 20th Centuries - I. A. Istomin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2023)
Despite the growing academic attention to the problem of interference in internal affairs, rhetorical techniques the state uses to legitimize interventions in the eyes of foreign counterparties, remain somewhat understudied in the Russian IR studies. In this regard, the case of the Monroe Doctrine, a landmark ideological construct in the history of international relations and US foreign policy, provides a unique framework for an in-depth study of the practices of legitimization and stigmatization of interventions. The paper examines the role of the doctrine in denouncing the interference of European powers in the domestic affairs of Latin American countries and justifying US actions in the region. The author outlines a set of issues related to legitimizing, both externally and internally, the actions of the state in the international arena. It is shown that the appeal to national interests suitable for solving the problems of domestic political legitimization, turns out to be ineffective in justifying interventions in the eyes of the international community and therefore gives way to references to established traditions and historical narratives. The paper examines the historical background of the 1823 presidential address and the ways how the US foreign policy establishment appealed to it later on, both to promote the idea of the inadmissibility of European interference in the affairs of the countries of the Western Hemisphere, and, subsequently, to justify American interventionism. Special attention is paid to the so-called Roosevelt Corollary, since it allows one to better understand the specifics of the US leaders’ perception of the Monroe Doctrine and to separate them from the distortions and stereotypes formed during the ensuing public debates and uncritically replicated in many academic studies. The author concludes that, though the Monroe Doctrine is regarded as a cornerstone of US foreign policy, in fact it played a limited role in both diplomatic justification and stigmatization of interventions. In this regard, it is more appropriate to consider it as a rhetorical asset rather than a strict guiding principle. In general, the case of the Monroe Doctrine reveals the situational conditionality of the practices legitimizing interventions, resulting in their limited persuasiveness. The latter seems to be almost inevitable given the constitutive importance of the institution of sovereignty for the maintenance of international society.